Childhood Amnesia in Children: A Prospective Study Across Eight Years. Issue 6 (3rd October 2017) - Peterson, Carole; Hallett, Darcy; Compton‐Gillingham, Cassy
Abstract : This was a prospective study of earliest memories across 8 years for 37 children who were of age 4–9 years initially. In three interviews (initial and after 2 and 8 years) children provided their three earliest memories; those from earlier interviews that were not spontaneously provided later were cued. There was little consistency in the earliest memory or overlap across interviews in spontaneous memories. The youngest group also forgot over half their initial memories although few were forgotten by older children. For consistency of content, 25%–32% of information by former 6‐ to 9‐year‐olds was the same after 8 years, but < 10% provided by the youngest children was the same and 22% was contradictory. Emotion and contextual coherence predicted memory retention.